The Art of Living: Meliorism in John Dewey and Confucius - Luque-Moya, Gloria (My University, 2022)
Meliorism has long been acknowledged to be central to pragmatist philosophy. However, despite the increasing interest has been risen in the recent years we barely find studies focuses on this important theme. Why? This doctrine, shared by classical pragmatists, is based on what Emerson calls the law of compensation, according to which “for every thing you have missed, you have gained something else”1. This approach is called optimistic, even naive, and has been harshly criticized because it presupposes, on the one hand, that nature is on our side, and on the other hand, that the "supposed evils" that we may suffer may only be apparent evils. The goal of my research is to establish the main features of meliorism in Dewey’s pragmatism through a comparative methodology. Since Dewey’s sixtieth birthday, several scholars have put Dewey and Confucius into dialogue because they are mutually elucidating. Presenting Dewey’s main ideas through a discussion of similar concepts in Confucian philosophy, we can explore the creative power of human life that both the American and Chinese thinkers defend.
Keywords: Pragmatismo - Congresos; Dewey, John (1859-1952) - Crítica e interpretación - Congresos; Confucio - Crítica e interpretación - Congresos; Confucius; Meliorism; Pragmatism; John Dewey